Calcium Soap Production from PFAD by Modified Fusion Method for Animal Feed - YULISTIA (NIM : 13014015) - FATHINAH ISLAMI HASYYATI (NIM : 13014055), DEA
Indonesia is the largest producer and exporter of palm oil in the world. In 2017, Indonesia produced 58.72% of total world palm oil. Palm Fatty Acid Distillate (PFAD) is a byproduct from distillation of crude palm oil which is mostly exported without being processed. PFAD is rich in free fatty acid. PFAD can be reacted with calcium oxide to produce calcium soap for animal feed. Calcium soap gives energy in protected fat form and can increase milk production in dairy cows. The unutilized of PFAD and the low milk production in dairy cows in Indonesia make PFAD potential to be used as the raw material at calcium soap production. This study aims to determine the effect of various operating conditions on the conversion of calcium soap reaction and compare it with a commercial product. Modified fusion method was used in producing the calcium soap in this study. The stoichiometric moles ratio of CaO:PFAD used is 1, 1.15, 1.2, or 1.4. The variations in initial temperature of reaction are 60°C, 70°C, 80°C, or 90°C. The variations in degree of CaO fineness reviewed are 28-48 mesh, 48-80 mesh, 80-100 mesh, or >100 mesh. The PFAD used is obtained from PT Tunas Baru Lampung Tbk and PT Smart Tbk. The free fatty acid content and moisture content of calcium soap were determined to quantify the quality of the product. Comparison of calcium soap with a commercial product is done through acid value, moisture content, and infrared spectrum analysis. The result of product analysis shows that the higher stoichiometric mole ratio of CaO:PFAD and degree of CaO fineness (depending on CaO content), the higher conversion achieved. Meanwhile, the higher initial temperature and the free fatty acid content of PFAD, the lower conversion achieved. Calcium soap produced using the best operating conditions gives results which are generally better than the commercial product.